2015
DOI: 10.1111/cei.12716
|View full text |Cite
|
Sign up to set email alerts
|

The impact of HLA class I and EBV latency-II antigen-specific CD8+ T cells on the pathogenesis of EBV+ Hodgkin lymphoma

Abstract: SummaryIn 40% of cases of classical Hodgkin lymphoma (cHL), Epstein–Barr virus (EBV) latency‐II antigens [EBV nuclear antigen 1 (EBNA1)/latent membrane protein (LMP)1/LMP2A] are present (EBV+cHL) in the malignant cells and antigen presentation is intact. Previous studies have shown consistently that HLA‐A*02 is protective in EBV+cHL, yet its role in disease pathogenesis is unknown. To explore the basis for this observation, gene expression was assessed in 33 cHL nodes. Interestingly, CD8 and LMP2A expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 68 publications
(111 reference statements)
1
35
0
Order By: Relevance
“…This contrasts sharply with EBV latent antigen-specific responses where examples of HLA-C restriction are extremely rare [8,37]. Finally, one of the more interesting comparisons between individual alleles involved HLA-A*0101 and A*0201 because of their identification as high and low risk alleles respectively for the development of EBV-positive Hodgkin lymphoma [38][39][40], a disease potentially linked to impaired T cell surveillance [39,41]. In that regard, previous studies have defined a small number of EBV latent and lytic epitopes restricted though A*0201, whereas numerous studies have failed to reveal any EBV-specific responses restricted through A*0101 [8,42].…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts sharply with EBV latent antigen-specific responses where examples of HLA-C restriction are extremely rare [8,37]. Finally, one of the more interesting comparisons between individual alleles involved HLA-A*0101 and A*0201 because of their identification as high and low risk alleles respectively for the development of EBV-positive Hodgkin lymphoma [38][39][40], a disease potentially linked to impaired T cell surveillance [39,41]. In that regard, previous studies have defined a small number of EBV latent and lytic epitopes restricted though A*0201, whereas numerous studies have failed to reveal any EBV-specific responses restricted through A*0101 [8,42].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of the HLA-A*02:01 allele in Europeans could be explained by common anti-EBV immune responses to antigens that are specifically presented by A*02:01 encoded HLA [28]. At the moment, it is unknown how HLA-A*01:01 and HLA-A*02:07 exert a risk effect, although this can be partially explained by lack of EBV latency type II responses in the context of these alleles.…”
Section: Discussionmentioning
confidence: 99%
“…The HLA background of cHL patients may also have a role in this respect and, more importantly, in dictating the inherent risk to develop an EBV‐positive cHL. Indeed, several studies have shown that the HLA‐A*02 allele is protective against EBV‐positive cHL, and this association has been recently substantiated by the demonstration that the subdominant T‐cell responses to LMP‐1 and LMP‐2 epitopes is largely confined to patients carrying this allele …”
Section: Microenvironmental Impact Of Ebv Infectionmentioning
confidence: 94%
“…Indeed, several studies have shown that the HLA-A*02 allele is protective against EBVpositive cHL, [69][70][71][72] and this association has been recently substantiated by the demonstration that the subdominant T-cell responses to LMP-1 and LMP-2 epitopes is largely confined to patients carrying this allele. 73 Tumor microenvironment of EBV-positive cHLs is also characterized by a more pronounced infiltration by macrophages as compared with EBV-negative cases. In fact, a prominent signature including the overexpression of macrophage-related genes was identified in EBV-positive cHLs by gene expression profiling of whole tumor tissues.…”
Section: Microenvironmental Impact Of Ebv Infectionmentioning
confidence: 99%